Intellectual humility and empathy among junior high school students in Yogyakarta: A correlational study - Rohmatus Naini; Ulfa Danni Rosada; Diki Herdiansyah; Mutiara Nuur Kamila; Wahid Aditiono (International Journal on Education Insight, 2026)
This study examines the association between intellectual humility and empathy among junior high school students in Yogyakarta, Indonesia. Using a quantitative correlational design, the research involved 208 students who completed standardized instruments measuring intellectual humility and empathy. We analyzed the collected data using Pearson’s product moment correlation. The results indicated a statistically significant and positive correlation between intellectual humility and empathy (, ), suggesting that higher levels of intellectual humility are associated with higher levels of empathy. Within the cultural context of Yogyakarta, which emphasizes politeness, mutual respect, and communal harmony, these findings provide empirical insight into the relationship between cognitive and socio-emotional dispositions. The study underscores the relevance of intellectual humility in adolescent character development and socio-emotional learning initiatives in school settings.